Template-free synthesis of oxygen-containing ultrathin porous carbon quantum dots/g-C3N4 with superior photocatalytic activity for PPCPs remediation. Issue 8 (26th June 2019) - Wang, Fengliang; Wang, Yingfei; Wu, Yuliang; Wei, Dandan; Li, Lei; Zhang, Qianxin; Liu, Haijin; Liu, Yang; Lv, Wenying; Liu, Guoguang
Abstract : We report, for the first time, the fabrication of an oxygen-containing ultrathin porous carbon quantum dots/polymeric carbon nitrogen metal-free composite with a highly enhanced photoresponse. Abstract : The development of facile and environmentally compatible synthetic strategies for broad-spectrum response photocatalysts is a primary goal for researchers in this area. For this study, we report on a template-free thermal treatment strategy for the synthesis of an oxygen-containing ultrathin porous carbon quantum dots/polymeric carbon nitride metal-free composites (CQD/OUPCN). Morphology characterization revealed that the thermal treatment induced bulk CQD/g-C3 N4 (CQD/BCN) to transform to porous ultrathin 2D nanosheets with a high specific surface area. Chemical structure characterization revealed that O atoms were involved in the chemical composition of C3 N4 following the introduction of CQD and subsequent thermal treatment. Optical and electrical characterization, as well as density functional theory (DFT) calculations, confirmed that the introduction of O atoms and CQD enabled the tuning of the intrinsic electronic state, and improved the charge transfer capacity of C3 N4 . Together with the up-converted fluorescence properties of CQD, the CQD/OUPCN exhibited remarkable broad-spectrum activity toward the degradation of PPCPs. Under visible light irradiation, the CQD/OUPCN-0.5% showed an 18.5 fold higher indomethacin (IDM) degradation rate than did g-C3 N4 . Further kinetics studies, including reactive species (RS) and degradation intermediate detection, indicated that RS, particularly O2 ˙ −, was generated during the photocatalytic process, which could lead to the decomposition, and finally mineralization of IDM.